Rock art sequences in uKhahlamba-Drakensberg Park, South Africa - Swart, J. (Southern African Humanities, 2021)
There are no secure regional chronologies for South African rock art. This limits the investigation of change and continuity in the practice of painting over time and space. In this paper, various rock art sequences from uKhahlamba-Drakensberg Park (UDP) are compared. The analysis includes two new sequences, from Ngwangwane 8 in the southern UDP and Eland Cave in the north, produced by applying the Harris Matrix. Several points of correspondence exist between the two new sites and other rock art sequences, especially Main Caves North in the central UDP. The analysis revealed an initial painting phase comprising monochrome humans and bichrome animals. No animals could be identified to species with confidence. Eland occur from Phase 2 onwards; rhebuck and other animals appear mid-sequence, indicating varying emphases in hunter-gatherer belief systems through time. The earliest human images are simple and monochrome. Human depictions become increasingly complex in mid-sequence, both in posture and colour. The most recent human images are relatively simple. Absolute dates associated with paintings correspond well with this painting sequence. Future research should comprise absolute dates based on relative sequences, integrated with contextual and ethnographic analysis.